Landscape analysis of family planning research, programmes and policies targeting young people in Jordan: stakeholder assessment and systematic review/Analyse globale de la recherche, des programmes et des politiques de planifcation familiale ciblant les jeunes en Jordanie : evaluation des parties prenantes et revue systematique - Gausman, Jewel; Othman, Areej; Dababneh, Abeer; Hamad, Iqbal; Dabobe, Maysoon; Daas, Insaf; Langer, Ana (Eastern Mediterranean health journal, 2020)
Background: Reaching married and unmarried young people in Jordan with family planning information and services is a priority, especially considering Jordan's large refugee populations. To date, dissemination of family planning research and programmatic experience targeting young people in Jordan has been limited. Aims: This study aimed to provide in-depth information on family planning intervention programmes, research and policies in Jordan that focus on young people aged 10-24 years. Methods: Data were gathered through a systematic review of peer-reviewed and grey literature related to reproductive health of young people, and focus groups discussions with stakeholders from 18 relevant governmental and nongovernmental organizations. Results: The literature review included 37 documents produced since 2008, which provide information at the individual, family/community, service delivery and policy levels. Young people in Jordan have limited knowledge of family planning methods and where to obtain family planning services. Little information is available on the availability of family planning services for young people. Several policy documents discuss family planning and reproductive health of young people in Jordan. Focus group discussions identified opportunities to integrate services and strengthen the development of future policies. Conclusions: The results of this study highlight key lessons learnt, opportunities for interventions and research gaps related to family planning among young people in Jordan. More attention should be paid to understanding and meeting the needs of Jordan's most vulnerable populations of young people, including urban refugees and married adolescents, especially as these populations continue to grow. Future programmes should build from past evidence and explore new areas and interventions. Keywords: adolescents, youth, reproductive health, family planning services, Jordan Contexte : Atteindre les jeunes mariés et non mariés en Jordanie en leur fournissant des informations et des services de planification familiale est une priorité, compte tenu notamment des importantes populations de réfugiés en Jordanie. À ce jour, la diffusion de la recherche en planification familiale et de l'expérience programmatique ciblant les jeunes en Jordanie a été limitée. Objectifs : La présente étude avait pour objectif de fournir des informations approfondies sur les programmes, la recherche et les politiques d'intervention en matière de planification familiale en Jordanie, centrés sur les jeunes âgés de 10 à 24 ans. Méthodes : Les données ont été recueillies par le biais des éléments suivants : un examen systématique de la littérature grise et examinée par des pairs concernant la santé génésique des jeunes ; et des discussions thématiques de groupe avec des parties prenantes de 18 organisations gouvernementales et non gouvernementales concernées. Résultats : L'examen de la littérature comprenait 37 documents produits depuis 2008, qui fournissent de l'information aux niveaux individuel, familial et communautaire, au sujet de la prestation des services et des politiques. Les jeunes Jordaniens ont une connaissance limitée des méthodes de planification familiale et des lieux où obtenir des services de planification familiale. On dispose de peu d'informations sur la disponibilité des services de planification familiale pour les jeunes. Plusieurs documents politiques examinent la planification familiale et de la santé génésique des jeunes en Jordanie. Les discussions thématiques de groupe ont permis de cerner les possibilités d'intégrer les services et de renforcer l'élaboration des politiques futures. Conclusions : Les résultats de la présente étude mettent en évidence les principaux enseignements tirés, les possibilités d'interventions et les lacunes de la recherche liés à la planification familiale chez les jeunes en Jordanie. Il convient d'accorder davantage d'attention à la compréhension et à la satisfaction des besoins des populations de jeunes les plus vulnérables de Jordanie, y compris les réfugiés urbains et les adolescents mariés, en particulier à mesure que ces populations continuent à croître. Les programmes futurs devront s'appuyer sur les données du passé et explorer de nouveaux domaines et interventions. [phrase omitted]